2012
DOI: 10.1099/vir.0.044149-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel polyomaviruses in South American bats and their relationship to other members of the family Polyomaviridae

Abstract: Bats are the natural reservoir of a variety of viruses, including a polyomavirus (PyV) from a North American brown bat. We investigated 163 spleen samples from 22 bat species from French Guiana for the presence of PyVs. In total, we detected 25 PyV-positive animals belonging to nine different bat species. Phylogenetic analysis was performed on the genomes of eight representative PyVs, and showed that the bat PyVs form three distinct lineages within the genus Orthopolyomavirus and are genetically different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…S5A) or the entire genome (SI Appendix, Fig. S5B) were similar and consistent with recently published phylogenetic analyses of LT genes from polyomaviruses (23)(24)(25). Strikingly, we found that one lineage of polyomaviruses that includes MCPyV and MPyV, as well as other polyomaviruses from primates, raccoons, rodents, bats, and one other human PyV, Trichodysplasia spinulosa-associated polyomavirus (TSPyV), all share the property of potentially encoding an overprinting ALTO/MT-like gene (Fig.…”
Section: Resultssupporting
confidence: 73%
“…S5A) or the entire genome (SI Appendix, Fig. S5B) were similar and consistent with recently published phylogenetic analyses of LT genes from polyomaviruses (23)(24)(25). Strikingly, we found that one lineage of polyomaviruses that includes MCPyV and MPyV, as well as other polyomaviruses from primates, raccoons, rodents, bats, and one other human PyV, Trichodysplasia spinulosa-associated polyomavirus (TSPyV), all share the property of potentially encoding an overprinting ALTO/MT-like gene (Fig.…”
Section: Resultssupporting
confidence: 73%
“…All digital control sequences ‘spiked’ into the data sets prior to bioinformatic analysis could be recovered correctly by both ways of data analysis, DTS and reference mapping. At the nucleotide level, the lowest homology hits matched a recently discovered bat polyomavirus [JQ958891.1 ] and Pan troglodytes verus polyomavirus (HQ385746.1). At the protein level, the hit with the weakest homology recovered was Gorilla gorilla gorilla polyomavirus (ADQ54205.1).…”
Section: Resultsmentioning
confidence: 93%
“…The focus on zoonotic RNA viruses has led to slower developments in understanding interactions between the bat immune system and DNA viruses. Multiple DNA viruses have been detected in bats, including herpesviruses (77-80), adenoviruses (81), hepadnaviruses (82), poxviruses (83) and polyomaviruses (81,84,85). These discoveries highlight the need to study antiviral responses to DNA viruses in bats.…”
Section: Sensing Dna Virusesmentioning
confidence: 99%